THE IMPACT OF GEOGRAPHICAL ASPECTS FOR AGRICULTURAL DEVELOPMENT IN UZBEKISTAN - Zeina Al-Saayigh (Mesopotamia Journal of Agriculture)
The last years of the current century witnessed an agricultural revolution in many developing and developed countries. This was achieved through the overlap of two main factors, the economic and geographical factors that control our daily lives and are considered among the most important factors that contributed major roles in the development of the agricultural sector. The economic aspect represents its role in how providing the necessary resources to increase agricultural output from various types of high-productivity inputs. As for the geographical factor, its role was represented in providing what the aforementioned sector needs in terms of land, water, heat and humidity for girls, given that these factors contribute together to achieving continuity in human life. Therefore, our study came to clarify how to use the factors Economic and geographical in achieving large-scale agricultural production sufficient to meet the need for self-sufficiency with the survival of a surplus for export, with an explanation of the mechanism performed or carried out by each sector with the intention of presenting it to researchers working in the field of agricultural research, especially in rural areas where the latest agricultural technologies are transferred to it with the aim of Adoption by farmers, and in order to achieve this goal, a number of economic factors have been used A number of researchers have prepared studies for this purpose.